2014
DOI: 10.1002/adfm.201304311
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Substrate and Processing on Confinement of Nafion Thin Films

Abstract: Thin films of ion‐conducting polymers are an important area of study due to their function in many electrochemical devices and as analogues for interfacial phenomena that occur in bulk films. In this paper, the properties of Nafion, a prototypical ionomer, are investigated as thin films (4 to 300 nm) on carbon, gold, and platinum substrates that are fabricated using different casting methods and thermal histories. Specifically, water uptake, swelling, and morphology are investigated by quartz‐crystal microbala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
389
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 193 publications
(420 citation statements)
references
References 71 publications
21
389
2
Order By: Relevance
“…However, the origin and existence of CPE cell , and CPE f in the impedance response of such systems are still under debate. 5,7,25,26 Soboleva et al 10 and Yadav et al 13 have indicated that Nafion membrane has a capacitance in parallel to the resistance. The origin of capacitance has been described as the polarization of water inside the nanopore and the close proximity of the sulfonate group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the origin and existence of CPE cell , and CPE f in the impedance response of such systems are still under debate. 5,7,25,26 Soboleva et al 10 and Yadav et al 13 have indicated that Nafion membrane has a capacitance in parallel to the resistance. The origin of capacitance has been described as the polarization of water inside the nanopore and the close proximity of the sulfonate group.…”
Section: Resultsmentioning
confidence: 99%
“…Film thickness and treatment protocols plus thermal history are the two influencing parameters on the proton conductivity of the Nafion nanothin films. For room temperature measurements (25 • C, Protocol-1), the proton conductivity of sub-55 nm Nafion thin films was found to be independent of thickness whereas that of the thicker films was thickness-dependent, approaching that of the membrane. The two distinct behaviors of the proton conductivity are highly consistent with the distinct surface wettability of the thin film.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies on the underlying knowledge of the structure/function relationships of ionomer thin-films in the catalyst layers are beginning to show that such an assumption is poor as discussed in more detail below. 157,[298][299][300][301][302][303][304][305] The kinetic expressions, equations 58 and 60 for the HOR and ORR, respectively, result in a transfer current between the electronicconducting (1) and ionic-conducting (2) phases (see equation 10), which is related to the current density in the two phases through equation 23 (neglecting double-layer charging)…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%